Various results in relation with the hypergeometric equations and the hypergeometric functions in the complex plane - IRMAK, Hüseyin (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The main purpose of this investigation is to specify an extensive relation between the hypergeometric functions and the hypergeometric equations in the complex plane and then to point various implications of our main result, conclusion and also recommendations out. Mathematics Subject Classification (2010): 30A10, 34A40, 33C05, 33C20, 33C45, 30C15, 33D15, 30D05, 33E20, 34K06, 37K20.